Total control - Baldacci, David (Grand central, 1997)
Total Heat Sidney Archer has the world. A husband she loves. A job at which she excels and a cherished young daughter. Then, as a plane plummets into the Virginia countryside, everything changes. And suddenly there is no one whom Sidney Archer can trust. Total Danger Jason Archer is a rising young executive at Triton Global, the world's leading technology conglomerate. Determined to give his family the best of everything, Archer has secretly entered into a deadly game.